Integrated generation of vortices and frequency conversion with metasurfaces - Jinyong Ma; Kenneth B. Crozier; Andrey A. Sukhorukov (Light: Science & Applications)
Abstract The generation of optical vortices in compact systems and across different spectral regions can open new horizons for their applications in end-user devices. Latest advances in the design and fabrication of optical metasurfaces made of a quadratically nonlinear material enable highly precise creation of vortices with different topological charges at the second-harmonic frequency, with the potential to obtain various other structured states of light.